Growth and productivity as influenced by nutrient management practices on Pigeon pea [Cajanus cajan (L.) Millsp.] in upland alfisols of Tripura - Ray, S; De, Biman; Hazari, S (SAARC Journal of Agriculture, 2015)
Pigeon pea [Cajanus cajan (L.) Millsp.] is the rich sources of dietary protein, carbohydrate & certain minerals but its poor yield needs to formulate a nutrient management practices for higher productivity in upland alfisols of Tripura and to combat it, an experiment was conducted during three consecutive kharif seasons at College of Agriculture, Lembucherra, Tripura comprising of two levels of Lime (150 and 200 kg ha-1) in main plot and two levels of molybdenum seed treatment (0 and 4g kg-1 of seed) in sub plot and 4 levels of recommended doses, viz., 0% of RDF ha-1, 50% of RDF ha-1, 75% of RDF ha-1 and 100% of RDF ha-1 (Recommended dose @ 20:60:40 of NPK). It was revealed that by the use of 100% RDF ha-1 with 150 kg ha-1 lime and 4g kg-1 of molybdenum seed treatment leads to higher yield and return per rupee respectively. But by the use of 100% RDF ha-1 with 200 kg ha-1 lime and 4g kg-1 of molybdenum seed treatment, return per rupee was recorded at 2.98. The investigation reflects that by the use of 75% RDF ha-1 return per rupee (3.78) was less compared to 100% RDF ha-1 but significant with saving the cost of 25% RDF ha-1 and soil health from the excessive use of fertilizer for sustaining the agricultural growth. SAARC J. Agri., 13(1): 123-134 (2015)